'Impermanence': A Translation of the First Chapter of the Tibetan Udānavarga. (30th November 2020) - Skilling, Peter
Abstract : The Udānavarga is a grand compendium of Buddhist verse, compiled by a Dharmatrāta about whom we know next to nothing. In Sarvāstivādin and Mūlasarvāstivādin circles the Udānavarga was as popular as is the Dhammapada in Theravādin circles, and it circulated widely in South and Central Asia. Here I give an English translation from the Tibetan of the first chapter, 'Impermanence'.